IMPLEMENTASI MANAJEMEN KELAS DALAM MENINGKATKAN MUTU PEMBELAJARAN PADA MATA PELAJARAN PAI DI UPTD SMP NEGERI 3 BIREUEN - Cut Irhamna Heriyanti; Ulfaturrahmi (Fakultas Tarbiyah IAI Almuslim Aceh, 2023)
The purpose of this study was to determine the implementation of classroom management in improving the quality of learning in PAI lessons at UPTD SMP Negeri 3 Bireuen. This research is qualitative with the type of field research. The research findings inform: First, an overview of UPTD SMP Negeri 3 Bireuen which is an educational unit with a junior high school level located at Bireuen Meunasah Reulet, Kota Juang District, Bireuen Regency. The facilities and infrastructure are sufficient to support an orderly and sustainable learning process. Second, the implementation of classroom management and the quality of learning can be done through planning, organizing, implementing and evaluating processes to achieve goals and create a conducive classroom climate for successful teaching and learning activities. Third, the implementation of class management in improving the quality of learning in PAI subjects at UPTD SMP Negeri 3 Bireuen includes indicators of successful classroom management which include creating conducive classes, the strategy of PAI teachers in establishing good cooperative relations with students, and the strategy of PAI teachers in managing study room in class. The components of learning quality include teachers, students, objectives, learning materials, learning activities, methods, learning tools, learning resources, and evaluation. Factors that influence classroom management include the physical environment, socio-emotional conditions, and organizational conditions.